ORLANDO COSTAS: ENSAIOS NO CAMINHO PARA UMA PASTORAL EVANGÉLICA LATINO-AMERICANA - Lima, Ricardo Barros (2008)
This research proposes an analysis of the Latin American evangelic pastoral proposed by Orlando Costas. An expert in missions and pastoral theology from Puerto Rico, Costas elaborated a pastoral method and methodology based on his evangelical, religious confession in ecumenical dialogue and in critical consonance with the political, economical, social and religious circumstances of Puerto Rico and Latin America. Costas, together with Emilio Castro, were the first theologians to offer the basis for an evangelic pastoral vision based on the experiences of Latin American people. He criticized North-Atlantic pastoral theology as a pastoral action centered on the pastor, which was professionally and ecclesiastically centered. The research is presented in three chapters. The first chapter presents the religious, social, economic and political context of the experience of Orlando Costas in Puerto Rico; the second deals with his conversion experience in the context of his religious tradition, and; the third presents his pastoral proposal, and analyses its theological and historical development, emphasizing the conferences, movements, institutions, and theologians who influenced Costas thought. It also demonstrates the vision of mission and theological basis for his evangelic pastoral. It demonstrates that Costas pastoral is missiological and pastoral, because it assumes the missi Dei as an architectonic principle and the pastoral as a hermeneutic principle for pastoral and mission action. The research concludes that Costas pastoral proposal is evangelic and ecumenical, contextual and autochthonous, both within and beyond the church.(AU)